IMPLEMENTASI KEBIJAKAN PROGRAM KARTU INDONESIA PINTAR DI SMAN 1 WONOAYU KABUPATEN SIDOARJO - Dona Amalia Wardana; Lailul Mursyidah (LPPM Universitas Abdurrab, 2025)
This research will analyze the implementation of the Smart Indonesia Card Program policy at SMAN 1 Wonoayu, Sidoarjo Regency using Warwic's policy implementation theory. The aim of this research is to describe the implementation of KIP policy at SMAN 1 Wonoayu according to Warwic's four factors of policy implementation theory. The research method applied is descriptive qualitative, with data collection techniques through interviews, observation and documentation. The results of this research are that the implementation of the KIP program at SMAN 1 Wonoayu is still not fully running well and effectively. It is evident from the results obtained that 2 of the 4 factors in Warwic's policy implementation theory are not fulfilled, namely the information factor in the form of data on KIP recipients is inaccurate so that many KIP distributions are still misdirected and the potential distribution factor is delays in disbursement of KIP funds due to lack of socialization about KIP to students So many complaints arise from KIP recipients